Potret Hukum Keluarga Muslim Di Nigeria, Somalia, dan Ghana: Regulasi Hukum Perkawinan dan Kewarisan yang berlaku bagi orang Islam di Nigeria, Somalia, dan Ghana - Andi, Dede; Mukhlas, Oyo Sunaryo; Khosyi’ah, Siah (Faculty of Law, Universitas Pekalongan, 2025)
Nigeria, Somalia, and Ghana are countries with distinct demographic compositions of the Muslim population: approximately 51% in Nigeria, 99% in Somalia, and 19.9% in Ghana. Each jurisdiction demonstrates diverse legal characteristics in the regulation of Muslim family law. This study aims to analyze the regulatory framework and the effectiveness of Muslim family law in these three jurisdictions. The research employs a descriptive-analytical method with a normative juridical approach. Data were obtained through a library-based examination of statutory provisions and relevant literature, and subsequently analyzed qualitatively. The findings indicate that the Federal Government of Nigeria has delegated authority to twelve northern states to regulate Muslim family law in accordance with Islamic law. Nevertheless, state involvement remains relatively minimal, as implementation is largely entrusted to local religious authorities, most of whom adhere to the Maliki school. In Somalia, the state assumes a dominant role through the codification and modernization of Islamic family law as embodied in the 1975 Family Law. By contrast, in Ghana, Muslim family law is regulated under the Mohammedan Marriage Ordinance (Cap 129 of 1951); however, the regulation is not comprehensive, with the state granting Muslim communities autonomy to observe Islamic law as a form of living law within society. The effectiveness of Muslim family law thus requires a balance between clear and comprehensive legal substance, robust institutional structures, and a legal culture supportive of its implementation